Über die Reduzierbarkeit eines n-dimensionalen Systems der Differenzialgleichungen - Merkys, V. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. М. Меркис. О проводимости одной n-мерной системы дифференциальных уравненийV. Merkys. Vienos n-matės diferencialinių lygčių sistemos redukavimas